2007
DOI: 10.11645/1.1.4
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of an information literacy training initiative at the University of Dar es Salaam

Abstract: PurposeThis paper reviews the implementation and impact of an Information Literacy Training course at the University of Dar Es Salaam in Tanzania. The purpose of the research which is described was to determine the effectiveness of different methods of assessment for teaching information literacy. MethodologyThe focus of the paper is an analysis of student learning through quizzes, exercises, reflective discussion and student presentations. The training lasted seven days and involved Masters Students fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Results in this section were aligned with Parirokh's findings that showed almost all the students’ have not adequate information literacy, and no significant difference was seen between information literacy skills of students before participating in the workshop. In addition, the results by Siamak, Alipur-Nodushan and Khaleghi[ 3 ] and Wema and Hepworth[ 15 ] that also examined the level of students’ information literacy in survey research method showed that that students’ information literacy is not in desirable level and is consistent with the results of this study. The results of Beyranvand and colleagues,[ 10 ] Hassanzadeh and Asadi,[ 11 ] Parirokh, Arastoopoor and Naderi,[ 12 ] Flaspohler,[ 14 ] Jorosi,[ 16 ] Jill and Aliki,[ 17 ] Lalor, Clarke and Sheaf,[ 18 ] and Kratochvil[ 19 ] that was in empirical and semi-empirical methods and through workshops compare and assess the students’ information literacy have indicated that the average of students’ information literacy was not in desirable level and before holding the course the students’ information literacy was not sufficient, the results of the present study was align to above mentioned findings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Results in this section were aligned with Parirokh's findings that showed almost all the students’ have not adequate information literacy, and no significant difference was seen between information literacy skills of students before participating in the workshop. In addition, the results by Siamak, Alipur-Nodushan and Khaleghi[ 3 ] and Wema and Hepworth[ 15 ] that also examined the level of students’ information literacy in survey research method showed that that students’ information literacy is not in desirable level and is consistent with the results of this study. The results of Beyranvand and colleagues,[ 10 ] Hassanzadeh and Asadi,[ 11 ] Parirokh, Arastoopoor and Naderi,[ 12 ] Flaspohler,[ 14 ] Jorosi,[ 16 ] Jill and Aliki,[ 17 ] Lalor, Clarke and Sheaf,[ 18 ] and Kratochvil[ 19 ] that was in empirical and semi-empirical methods and through workshops compare and assess the students’ information literacy have indicated that the average of students’ information literacy was not in desirable level and before holding the course the students’ information literacy was not sufficient, the results of the present study was align to above mentioned findings.…”
Section: Discussionsupporting
confidence: 88%
“…He also mentioned that the collaboration of the library and university is fundamental for information literacy education. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…In recent years however, interest in IL and its contribution to teaching and learning has emerged and a number of studies in IL issues have been conducted. Such studies include those by Wema and Hepworth (2007); Lwehabura and Stilwell (2008); and Chilimo (2008). Currently, higher education institutions in Tanzania, universities in particular, practice various forms of programmes.…”
Section: Information Literacy Education In Tanzaniamentioning
confidence: 99%
“…In attempting to ascertain the contributions of IL training to learners at UDSM, two studies were conducted: Wema and Hepworth, (2007) and Klomsri and Tedre, (2016). Wema and Hepworth, (2007) assessed the effectiveness of methods for teaching IL while Klomsri and Tedre, (2016) examined students’ levels of IL skills, perceptions and ways of improving pedagogical methods used to deliver IL training. Even though these studies laid a corner stone in understanding the effectiveness of IL training at UDSM, there is a need to take a different approach to see what IL skills users demonstrate when using one of the information retrieval systems, the OPAC.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005 the University of Dar es Salaam Library introduced an IL programme to undergraduate and postgraduate students. The inception of the IL programme was part of the PhD study aimed at developing a programme and a framework for teaching IL in public university libraries in Tanzania (Wema and Hepworth, 2007). Since then, the IL programme has been implemented in the form of non-credit-based training courses to faculties, postgraduate and undergraduate students.…”
Section: Introductionmentioning
confidence: 99%